Welding with high power fiber lasers - A preliminary study. - Quintino, Luísa; Costa, A.; Miranda, R.; Yapp, David; Kumar, Vinod; Kong, C. J. (Elsevier, 2007)
The new generation of high power fiber lasers presents several benefits for industrial purposes, namely high power with low beam divergence, flexible beam delivery, low maintenance costs, high efficiency and compact size. This paper presents a brief review of the development of high power lasers, and presents initial data on welding of API 5L: X100 pipeline steel with an 8 kW fiber laser. Weld bead geometry was evaluated and transition between conduction and deep penetration welding modes was investigated.
Keywords: X100 steel; Fibre lasers; Welding